Homeless shelter food production: positive implications for clients and volunteers - Suzanne Mills-Wasniak; Christopher Penrose; Brian Raison; Roger N. Reeb; Katie Gibbins; Amanda Barry; Lara Khalifeh; Tia Turner; Alea Albright (Urban Food Systems Symposium, 2020)
Within the context of a longstanding project (Behavioral Activation Project in Homeless Shelters), the Shelter Farm was developed on the grounds of a homeless shelter located in a food desert. The Behavioral Activation Project, which represents a decade-long collaboration between a Professor of Psychology at the University of Dayton (Roger N. Reeb, Ph.D.) and St. Vincent de Paul (Dayton, Ohio), fosters self-sufficiency in shelter residents as they strive to overcome personal challenges and obstacles associated with homelessness. Past research shows that the Behavioral Activation Project enhances the psychological (and adaptive) functioning of shelter residents as well as the civic-related development of service-learning students who assist in implementing the Project. In 2017, Dr. Reeb (University of Dayton) established a collaboration with Ms. Mills-Wasniak (Extension Educator, The Ohio State University Extension Montgomery County) to develop the Shelter Farm at the St. Vincent de Paul Gettysburg Gateway Shelter for Men. A Memorandum of Understanding among the three collaborative entities was developed and approved. Shelter residents volunteered to work alongside service-learning students and community partners on the farm. In the first season, we harvested nearly a ton of produce – all of which was delivered to the shelter kitchen to enhance the nutrition of shelter residents. The Shelter Farm also enhanced St. Vincent de Paul’s budget for food, as we estimated wholesale value of the produce at almost 4,000. This same level of success was replicated in Shelter Farm’s second season. As we faced COVID-19 obstacles in the third season, safety protocols were approved by all three aforementioned collaborative entities, and we sustained the Shelter Farm, harvesting approximately 1500 pounds of produce for the shelters. In the first season, a graduate student in clinical psychology at the University of Dayton completed an M.A. Thesis providing preliminary evidence that, as shelter residents volunteer to work alongside students and community partners on the farm, they show decreases in state anxiety and improvements in wellness over time. This manuscript provides the following: (a) a description of the long-standing Project that provided the infrastructure for developing the Shelter Farm, (b) a description of the collaborative process underlying the initiative, the Shelter Farm itself, and the success in sustaining the Shelter Farm, even in the face of COVID-19; (c) an overview of the benefits (nutritional and psychological) of the Shelter Farm for shelter residents; and (d) plans for sustaining and expanding the Shelter Farm (and associated research).
Keywords: shelter farm; homeless shelters; urban farming; behavioral activation; vulnerable community members; service-learning pedagogy